2015
DOI: 10.1111/ejh.12600
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity profile of repeated doses of PEG‐asparaginase incorporated into a pediatric‐type regimen for adult acute lymphoblastic leukemia

Abstract: Despite having been long regarded as too toxic for adult patients, pediatric-like regimens containing L-asparaginase have resulted in improved outcomes for adults with acute lymphoblastic leukemia (ALL). To characterize the spectrum of toxicity of repeated doses of polyethylene glycolated-asparaginase (PEG-asp) in adults, we reviewed all doses (2000 IU/m(2) ) administered as part of a pediatric-inspired regimen in adult ALL at our center. Subjects aged 18-60 yr with ALL (n = 152, 69.1% male) contributed 522 do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
81
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(86 citation statements)
references
References 15 publications
3
81
2
Order By: Relevance
“…[44,45] Within the last 15 years, reported rates of hypersensitivity in clinical trials have varied across studies using different routes of administration and asparaginases (Table 2). [14,[23][24][25]34,38,42,[46][47][48][49][50][51][52][53][54][55][56][57][58][59][60] Recently, a number of retrospective reports have compared the incidence of hypersensitivity between IV and IM PEG-asparaginase (Table 3). [8,34,[60][61][62][63][64] In a pediatric study of 318 patients, Petersen et al reported a 9% greater incidence of hypersensitivity following IV administration of PEG-asparaginase compared with IM PEG-asparaginase (p ¼ .028).…”
Section: Asparaginase Pharmacokineticsmentioning
confidence: 99%
“…[44,45] Within the last 15 years, reported rates of hypersensitivity in clinical trials have varied across studies using different routes of administration and asparaginases (Table 2). [14,[23][24][25]34,38,42,[46][47][48][49][50][51][52][53][54][55][56][57][58][59][60] Recently, a number of retrospective reports have compared the incidence of hypersensitivity between IV and IM PEG-asparaginase (Table 3). [8,34,[60][61][62][63][64] In a pediatric study of 318 patients, Petersen et al reported a 9% greater incidence of hypersensitivity following IV administration of PEG-asparaginase compared with IM PEG-asparaginase (p ¼ .028).…”
Section: Asparaginase Pharmacokineticsmentioning
confidence: 99%
“…The L-glutaminase activity of these bacterial L-asparaginases is significant, ϳ2% of the EcA activity and as high as 10% for ErA (3). Of note, the L-glutaminase activity of the clinically used L-asparaginases has been implicated in many of the side effects of this treatment, which include immunosuppression (2, 6, 7), hepatotoxicity (8), pancreatitis (9), and coagulation dysfunction (9,10). Many of the side effects are believed to be due to the disruption of protein synthesis induced by the L-glutaminase activity of L-asparaginase drugs (2,7,8,11,12).…”
mentioning
confidence: 99%
“…While different forms of the drug offer multiple options for patients who experience allergic reactions, all forms are associated with metabolic complications that are difficult to predict, yet intensify with age (1,2,13,16,22,28,31,50,52,62).…”
mentioning
confidence: 99%